The Islamic State: A Conceptual Framework (American Journal of Islam and Society, 1991)
IntroductionThe purpose of this paper is to delineate the basic elements involvedin the concept of the Islamic state and to clarify the basis and scope of politicalpower. More specifically, discussions will focus on the purpose of the Islamicstate, the source of political legitimacy, and the scope of state power. I willcontend that a clear distinction should be made between the role and purposeof the state and those of the ummah, for only through the separation of theresponsibilities and objectives of the two can the injunctions of the Shari‘ahand the principles of revelation be properly observed.Historical BackgroundAlthough the word “state” (dawlah) was first used in the Qur’an, almostsix centuries had to elapse before the word was given its first technical definitionby Muslim scholars. The word dawlah was mentioned once in the Qur’an(in 59:7) in connection with the distribution of the fay’ (the property Muslimsappropriated from the Banu al Nadr upon the latter‘s expulsion from Madinah).The Qur’an justified this departure from the usual practice of dividing thespoils among the fighters by referring to the divine intention of preventingthe circulation of wealth among a small group within the society?Up until the late fifth century, one could hardly find any reference tothe state in Muslim literature, or in Western literature for that matter. Otherterms such as al amsar or dar al Islam were employed whenever a referencewas made to the territories under Muslim control. Alternatively, the stateas a political body was identified by its political organs, i.e., al khilafah, ...